2015
DOI: 10.1111/ecog.01322
|View full text |Cite
|
Sign up to set email alerts
|

The importance of species pool size for community composition

Abstract: We investigated if an increase in species pool size leads to more pronounced turnover in local communities and assessed if this increase relates to stronger competition for environmental niches or to more random placement of species. We compared compositional turnover of pteridophytes (ferns and lycophytes) at 15 sites in mountain ecosystems on 13 islands in southeast Asia and Melanesia that mainly differed in the size of their species pool. Each site was sampled with 16 plots of 20 × 20 m2. Using multiple reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 73 publications
(108 reference statements)
0
37
2
Order By: Relevance
“…However, there are few in‐depth microclimatic measurements to assess relative contributions of cloud‐driven air moisture and precipitation to cloud forest plants. Nevertheless, an assessment from Costa Rica showed that, although the precipitation peak was situated at about 1000 m, air humidity was highest at about 2,000 m (Kluge et al., ), as also supported by assessments of tree bryophyte cover as a proxy of air humidity (Karger et al., ). As a large amount of fern diversity is actually epiphytic (up to 62% especially in our tropical and subtropical gradients), water is supplied to them by air moisture rather than through rainfall.…”
Section: Discussionmentioning
confidence: 85%
“…However, there are few in‐depth microclimatic measurements to assess relative contributions of cloud‐driven air moisture and precipitation to cloud forest plants. Nevertheless, an assessment from Costa Rica showed that, although the precipitation peak was situated at about 1000 m, air humidity was highest at about 2,000 m (Kluge et al., ), as also supported by assessments of tree bryophyte cover as a proxy of air humidity (Karger et al., ). As a large amount of fern diversity is actually epiphytic (up to 62% especially in our tropical and subtropical gradients), water is supplied to them by air moisture rather than through rainfall.…”
Section: Discussionmentioning
confidence: 85%
“…The perception of processes that shape local community composition and diversity largely depends on the circumscription of the species pool (Kraft et al ., ; Anacker & Harrison, ; Lessard et al ., 2012a,b; Karger et al ., , ) and how this relates to the spatial and temporal scale of sampling (Tuomisto & Ruokolainen, ). Incorporating the probabilistic species pool into studies on community composition and diversity can help disentangle the strength of different processes that drive local species assembly and their geographical distribution.…”
Section: Prospects and Limitations Of Probabilistic Species Poolsmentioning
confidence: 99%
“…This varying combinations of factors allows the use of elevational gradients to disentangle the relative effects of different factors. Second, most mountains are spatially constricted to different geographical regions, implying that they have uniform regional species pools (Karger et al, ), which allows to address questions regarding the role of historical factors in determining the composition of communities (Rahbek et al, ; Karger et al, ; Lessard et al, ).…”
Section: Elevational Gradients As Systems To Study Evolutionary and Ementioning
confidence: 99%